Rate and Predictors of Infant Abandonment among Unmarried Mothers at a Public Hospital in Kedah, Malaysia: A retrospective study - Mohd Suan, Mohd Azri; Soelar, Shahrul Aiman; Chan, Huan Keat (Thai Journal of Obstetrics and Gynaecology, 2018)
Objectives: This study aimed to determine the rate of unmarried mothers who decided to abandon their infants at the Hospital Sultan Abdul Halim, Kedah, Malaysia and the predictors that influenced such decisions. Materials and Methods: A retrospective study was conducted on unmarried mothers who gave birth at the hospital between January 2011 and December 2013. Information about their sociodemographic and clinical characteristics and their decisions on whether to abandon their infants was obtained from medical records. Furthermore, the predictors of infant abandonment were identified through binary logistic regression analysis. Results: Of the 266 unmarried mothers included in this study, nearly half were aged less than 20. Most of them were Malay, unemployed and first-time mothers with a generally low educational level and income. Fifty (18.8%) of them decided to abandon their children, and the predictors of making such decisions included being aged 30 or above (adjusted odds ratio [aOR] 3.33 [95% confidence interval CI 1.21–9.15]), having rape-related pregnancy (aOR 5.89 [95% CI 2.10–16.53]) and having unemployed male partners (aOR 3.10 [95% CI 1.50–6.39]). Conclusion: This study revealed that infant abandonment was common in the studied area, particularly among unmarried mothers with complex social factors. The factors that can be used to predict decisions on infant abandonment included the mother’s age, rape-related pregnancy and employment status of the male partner. Keywords: abandonment, infant, Malaysia, unmarried mother.